Semiconductor HPHT-diamonds as active elements of electronic devices: their structural and electronic properties - Kovalenko, T.V.; Nikolenko, A.S.; Ivakhnenko, S.O.; Strelchuk, V.V.; Lytvyn, P.M.; Danylenko, I.M.; Zanevskiy , O.O. (Reports of the National Academy of Sciences of Ukraine, 2021)
Structurally perfect diamond single crystals of type IIb doped with boron with developed growth sectors 113 and 110 are grown by the HPHT- crystallization method. Single-sector semiconductor diamond plates are obtained by the predicted cutting of crystals by mechanical and laser treatments using the developed microphotogrammetric 3D modeling of the sector structure. Raman and IR spectroscopies have been used to study the structural perfection and peculiarities of the defect-impurity composition of crystals. The electronic properties of growth sectors and intersectoral boundaries are characterized by the non-contact method of force Kelvin probe microscopy. The necessity of using certain optical and electrophysical diagnostic methods of p-type semiconductor material certification and the prospects of using single-sector semiconductor wafers for the development of Schottky diode designs are demonstrated.